E-business transformation of a chinese music house. - Goh, Christine Beng Li. (2008)
This dissertation looked at business opportunities for chinese pop music in the Asia Pacific and how these opportunities can be taken up by EWH to become Asia Pacific most preferred supplier of original chinese pop music.